The evaluation of working through projects by students: a study based on an university innovation project - Rafael Crismán Pérez; José Mª Cardeñoso; Esther García-González (Universitat Politècnica de València, 2017)
This paper focuses on an Innovation Teaching Project in the University of Cadiz during the academic year 2014/15. This  project  consisted  of  applying  a  work methodology  by  projects  to  all  groups  of students in third grade of Early Childhood Education   Teachers.   In   this   way,   we used a sample of 123 participants.  Two factors  were  measured:  programming  by projects  contents  and  key  competences by  university  students  in  Early  Childhood Education   and   the   university   teaching La evaluación del trabajo por proyectos por los estudiantes: un estudio a partir de un proyecto de innovación docente innovation as key factor in the learning of students.  The results showed a positive attitude   by   the   students   towards   the measured factors.  In addition, students putted the emphasis on strategies of cooperative learning or the teaching innovation as key factors of teaching (Sancho; Burundian; Apodaca; Lobato; San José and Zubimendi, 2010;   Pegalajar   and   Colmenero,   2013). Furthermore,   the   participants   showed the    importance    of    the    feedback    in the   teaching-learning   process   and   the autonomy in the management by tasks in this work methodology.  This  research displayed  the  necessity  of  an  adequate teaching  coordination  to  carry  out  this methodology by projects and the benefits of self-assessment for students and for the external evaluators to evaluate cooperative learning team.